Kesadaran Karier dan Pengambilan Keputusan Karier di Kalangan Mahasiswa Indonesia: Peran Mediasi Kelompok Sebaya dan Perbedaan Gender - Noviekayati, I Gusti Ayu Agung; Pratitis, Niken Titi; Bata, Pricilla Rosdinata Lese Mari; Azzahra, Aninditha (ANIMA Indonesian Psychological Journal, 2026)
Career decisions are important for university students in planning their future careers after graduation. This study examined the influence of career awareness on career decision making, with peer group as a mediating variable. In addition, the mediation model was tested separately among male and female students. The study was conducted in three cities in East Java, Indonesia (Jember, Surabaya, and Malang). Participants were selected using purposive sampling, resulting in a final sample of 303 students in their 5th Semester or above. Data were collected using the Career Awareness Scale, Peer Group Scale, and Career Decision-Making Scale. Mediation analysis with bootstrap procedures was conducted using JASP 0.18.2.0 for Windows. The results showed that career awareness had a positive and significant effect on career decision making (β = .459, p < .001). Peer group significantly mediated the relationship between career awareness and career decision making (β = −.127, p < .001). The negative indirect effect suggests that peer influence may weaken the positive contribution of career awareness to autonomous career decision making. Gender-based analyses revealed that career awareness positively influenced career decision making among both male and female students. However, the mediation effect of peer group was significant among female students (β = −.062, p = .036) but not among male students (β = −.082, p = .063), indicating gender differences in the role of peer influence. These findings highlight the importance of career awareness as a key predictor of career decision making and demonstrate that the influence of peer group varies across gender groups.